A RESEARCH OF POST-TRAUMATIC STRESS AND ADAPTATION DISORDERS OF SERVICEMEN AFTER BEING IN A COMBAT SITUATION AT THE HOSPITALIZATION STAGE - Shevchenko, Rosina; Hrys, Antonina; Pavliuk, Mariya; Stynska, Viktoriia; Babiak, Olha; Zavatskyi, Vadym; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the article is to study the characteristics of the psychophysiological state of servicemen with post-traumatic stress disorders (PTSD) and adaptation disorders (AD) after being in combat conditions. The research was implemented at the hospitalization stage, a comparative characteristic of the level of reactive and personal anxiety of the studied, according to the autonomic, sensorimotor, affective and ideator registers, was carried out. Methods used: observation, conversation, the questionnaire “Scale of self-assessment of reactive (situational) and personal anxiety (“SSRPA”) (Spielberger, 1983; adapted by Hanin, 1983). According to the received results, in the group of servicemen with PTSD: in the affective register – complaints of a feeling of sadness, experiencing a state of melancholy, obsessive memories of experienced events; in the ideator register – a state of confusion. In the group of military personnel with AD: in the affective register – unmotivated anxiety, periods of intolerance towards oneself, irritability, difficulties in selfcontrol. A study of the level of reactive and personal anxiety of the studied confirmed the presence of a more pronounced pathogenic picture of servicemen with adaptation disorders.